CRANIOFACIAL ANTHROPOMETRY CHARACTERISTIC AND DERMATOGLYPHICS PATTERN AMONG SCHIZOPHRENIA SUBJECTS IN JAVANESE ETHNIC OF INDONESIA - Cahayani, Wike Astrid; Adiba, Rizqi Hasna; ‘Aisy, Nabilah Rohadatul; Widyanto, Ilham Aditya; Sunardi, Adisty Aulia Kamarani; Ramadhan, Yanuar; Yudhantara, Dearisa Surya; Kurnianingsih, Nia (MNJ (Malang Neurology Journal), 2025)
Background: Craniofacial dysmorphology and dermatoglyphic abnormalities in schizophrenia patients are hypothesized to reflect neurodevelopmental disturbances during embryogenesis. These markers may serve as cost-effective, non-invasive tools for identifying individuals at risk of schizophrenia. Objective: This study aimed to explore craniofacial anthropometry and dermatoglyphic profiles as potential early markers of schizophrenia in the Javanese ethnic population. Methods: A cross-sectional study was conducted involving 30 schizophrenia patients and 30 matched healthy controls. Craniofacial measurements (cephalic, facial, and nasal indices) were obtained, and fingerprint patterns were analyzed for dermatoglyphic traits. Statistical comparisons employed unpaired T-tests and Mann-Whitney tests. Results: Significant differences were observed in facial index (P<0.01) and nasal index (P<0.05) between schizophrenia and control groups, with hyperleptoprosopic facial types dominating in schizophrenia patients (56.7%). Dermatoglyphic analysis showed no significant differences; however, a higher prevalence of loop patterns and reduced whorl patterns were noted in the schizophrenia group. Conclusion: Craniofacial anthropometry demonstrates promising potential as an adjunctive marker for early schizophrenia risk detection, particularly in resource-limited settings where advanced diagnostic tools are unavailable. Although dermatoglyphic patterns revealed limited statistical significance, observed trends highlight the need for further studies. These findings provide a basis for developing population-specific screening programs and contribute to the understanding of ethnic-specific neurodevelopmental markers.